1998
DOI: 10.1212/wnl.50.6.1842
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind randomized trial of tramadol for the treatment of the pain of diabetic neuropathy

Abstract: The results of this placebo-controlled trial showed that tramadol was effective and safe in treating the pain of diabetic neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
234
1
20

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 501 publications
(257 citation statements)
references
References 0 publications
2
234
1
20
Order By: Relevance
“…It is an effective agent in the treatment of painful diabetic peripheral neuropathy compared with placebo as demonstrated by two large multicenter trials (129,130), and it appears to have long-term effects (131). Although tramadol has a lower potential for abuse compared with other opioids, given these safety concerns, it is not recommended for use as first-or second-line agent.…”
Section: Opioid and Atypical Opioid Analgesicsmentioning
confidence: 99%
“…It is an effective agent in the treatment of painful diabetic peripheral neuropathy compared with placebo as demonstrated by two large multicenter trials (129,130), and it appears to have long-term effects (131). Although tramadol has a lower potential for abuse compared with other opioids, given these safety concerns, it is not recommended for use as first-or second-line agent.…”
Section: Opioid and Atypical Opioid Analgesicsmentioning
confidence: 99%
“…Because of codeine's genetic variability in its rate of metabolism, its use should be individualized. 51 Tramadol is a synthetic analog of codeine that has shown efcacy in neuropathic pain, 52 but has no anti-infammatory activity. It can increase the risk of seizures and serotonin syndrome because it is also a monoamine reuptake inhibitor.…”
Section: Reviewmentioning
confidence: 99%
“…A recent study in Greece found pregabalin to be more cost effective as compared to gabapentin [73]. A double blinded randomised trial study of tramadol has been proven to be successful in alleviating pain symptoms in diabetic neuropathy [74]. Aldose reductase inhibitors are being studied and have shown to be effective in inhibiting progression of peripheral neuropathy [75,76].…”
Section: Medical Treatmentmentioning
confidence: 99%